Synthesis and characterization of a low-cost aerogel structure using classical drying methods for thermal insulation. Issue 2 (10th April 2017) - Nachawaty, Abir; Bassil, Maria; Choueiry, Antoine; Tahchi, Mario; Habchi, Roland
Abstract : Purpose: Lightweight insulators are of major importance for the industry, in particular for thermal insulation in buildings. The purpose of this paper is to present a low-cost method to obtain aerogels with high insulating properties. Design/methodology/approach: Silica aerogel structures have been obtained by a low-cost sol-gel synthesis method. Surface modification, using dimethyldichlorosilane and trimethylchlorosilane, has been applied in order to get different thermal and optical properties. Findings: The samples show very promising thermal properties as tested through an infrared camera observation. A 5-mm-thick piece of aerogel is able to withstand the temperature of a brazing flame and reduce the heat by at least 150 degrees on its opposite side. The samples have a vitreous like structure as observed by SEM, some surface cracking is observed but they stay within acceptable limits. Originality/value: A very good thermal insulator is obtained with a very simple and low-cost method. The bulkiness of the supercritical drying is eliminated and the obtained structure has good properties.